NeWWWsDOTCOM an analytical study on online news : the August 23 Manila hostage-taking incident - Porras, Rochelle Macahipay 1988- (Quezon City College of Mass Communication, University of the Philippines Diliman, 2011)
"The study examined the similarities and differences revealed in the online news articles in their portrayal of the Manila hostage-taking incident on August 23,2010. Data were selected from four countries: the Philippines, China, United Kingdom and the United States of America. To determine these similarities and differences, the study analyzed the forty available articles published August 23 and 24, 2010 on the Internet. These articles were retrieved from online news sources: ABS-CBN News (http//:www.abs-cbnnews.com); GMANews.TC (http//:www.gmanews.tv); The Philippine Star Online (http//:www.philstar.com); Beijing Review (http://bjreview.com.cn/); The Standard (http://thestandard.com.hk); Xinhua Online (http://news.xinhuanet.com); BBC News (http://www.bbc.co.uk/news); The Guardian (http://guardian.co.uk); Reuters (http://www.reuters.com) CNN.com (http://www.cnn.com); FoxNews.com (http://foxnews.com); and The New York Times (http://www.nytimes.com). The researcher used computer-aided content analysis and found out that the news articles portrayed the hostage-taking incident as positive, negative, neither positive nor negative, and both positive and negative accordingly apart from reporting the good and/or the bad in this "bad" news. In the process, the study showed how news amongst online sources, and on top of that amongst four countries, vary significantly."
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman